Merajut Keberagaman dalam Upaya Menumbuhkembangkan Kehidupan yang Harmonis Penuh Cinta di Kota Ternate - Putri, Sri Haryati (Jurnal Sejarah Indonesia, 2023)
Ternate grows and develops with all its cultural diversity. This country is the land of kings. As a region that is the center of the spice trade, the city of Ternate has become a stopover for various nations in the world. Therefore, Ternate is called a city that is friendly and open to anyone. The purpose of this writing is to reveal that, as can be seen until now, Ternate with its historical might has made its region so authentic. Both are seen from the various relics and historical evidence that are still preserved today. By using the historical research method, which consists of heuristics, criticism, interpretation and writing, if the people of Ternate are a plural and multicultural society. This is a long historical process from the past to the present. Therefore, Ternate City is inhabited by various ethnicities. Such as Java, Sulawesi, Minang, Arabic, to Chinese. Of course they live in a different cultural, religious, linguistic order. However, differences are not a threat. entertaining both indigenous and immigrant communities can live side by side. Open life and love each other. So that it is called the region with the happiest population in Indonesia.